Interrelation of the Сulture and Historical Consciousness in Terms of Developing a Modern Value Paradigm - Shestakov, Yuri A. (Journal of History Culture and Art Research, 2019)
This paper reveals what foundations of the value paradigm of modern society are the most appropriate to contemporary cultural and historical realities on the basis of the study of interrelation between cultural phenomena and historical consciousness. The study employs a significant range of methodological and theoretical approaches of philosophy, cultural and social studies. The article argues that three different approaches to interrelation of culture and historical consciousness are correlated with three approaches to the establishment of the value paradigm of modern society. The author considers that the most suitable axiological basis for the establishment of the value paradigm in modern social and cultural situation is the principle of individual autonomy that will help to strike a balance of values of personalistic egoism, national and corporate altruism, and also humanistic universalism. The historical consciousness developed within this value paradigm makes it possible to overcome both an objectivist interpretation of historical path typical for classical science and a subjectivist one common to post-modern historical philosophy.